Behring Sea Arbitration. Supplementary report of the British Behring Sea Commissioners, January 31, 1893. - Great Britain. Bering Sea Commissioners.; Dawson, George Mercer, 1849-1901.; Baden-Powell, George Smyth, 1874-1898, Sir.; Bering Sea Tribunal of Arbitration. ([London?, 1893)
Signed: George Baden-Powell, George M. Dawson. Mode of access: Internet.